PENERAPAN PEMBINAAN INDIVIDU UNTUK MENINGKATKAN KEDISIPLINAN DAN KINERJA GURU BARU - Edy Susanto Edy Susanto (Manajer Pendididikan, 2015)
The objective of this research was to know whether the implementation of individual coaching by head teacher can increase new teacher’s discipline and job performance and to know how the effectivity implementation of individual coaching. The method of this research was action research. The result of this research obtained from average of discipline score and job performance score. In average of discipline score for the first cycle obtained score 36,61, the second cycle obtained score 52,26 and the third cycle obtained score 75,14 that means very good categorized. In Average of job performance score for the first cycle obtained score 121,67, the second cycle  obtained score 152,16 and the third cycle obtained score 183,67 that means very good categorized.Keywords: individual coaching, discipline, job performance